PENDETEKSIAN BATAS-BATAS ZONA STEAMFLOOD MENGGUNAKAN DATA ANOMALI GAYABERAT-MIKRO 4D YANG DIBERI KONSTRAIN - Fauzi, Ahmad; A. Kadir, Wawan Gunawan; Dahrin, Darharta; Santoso, Djoko (Sainstek, 2009)
Recently, the oil industry has emphasized enhancement oil recovery (EOR) process. The steamflood are ones EOR process can used to increase the heavy oil production. Effective management of EOR process requires detailed reservoir description and observation of the reservoir being swept at time. The 4D microgravity method can be applied in obtaining reservoir description such as steamflood zone mapping. Combination between the rock physics analysis with ideal model of steamflood used to calculate the synthetic 4D microgravity anomaly. This result suggest the negative 4D microgravity anomaly changes at time represented steamflood zones causes by density contras between steam at the high temperature after injection and pressure with heavy oil at the low temperature and pressure before injection. But the 4D microgravity anomaly can’t detect steamflood zone boundaries causes the anomaly shape with respect to shape of source. We proposed the 4D microgravity anomaly constrained with high resolution horizontal derivative to detect steamflood zones boundaries. The field data showed gravity change of up to -300mGal have occurred in area near ones the oil production well.  The maxima value of the field constrained 4D microgravity anomaly represented the steamflood zones boundaries with its surrounding. Key Word :     EOR process, steamflood, rock physics analysis, the constrained 4D microgravity anomaly